Sildenafil citrate on the inducibility of ventricular fibrillation and upper limit of vulnerability in swine - Kanlop N. (2014)
Background: Sildenafil citrate at supratherapeutic levels has been reported to decrease defibrillation efficacy. However, its effects on ventricular fibrillation induction and the upper limit of vulnerability (ULV) have not been investigated. We tested the hypothesis that sildenafil citrate reduces the ventricular fibrillation threshold (VFT) and increases the ULV. Material/Methods: Twenty-one pigs (25-30 kg) were randomly assigned into 3 groups of 7 pigs each. A solution containing 100 mg (group 100) or 50 mg (group 50) sildenafil citrate or 100 cc saline (group control) was infused intravenously in each pig. A train of 10 S1s was delivered from an RV electrode, and an S2 stimulus was delivered at the peak of the T wave of the last S1 activation to determine the VFT and ULV, before and after drug administration. Results: The 100 mg sildenafil citrate significantly (P<0.03) decreased VFT, accounting for ∼36% by peak voltage and ∼52% by total energy, and significantly (P<0.009) increased ULV, accounting for ∼28% by peak voltage, and ∼56% by total energy. Conclusions: Supratherapeutic concentrations of sildenafil citrate significantly decreased the VFT and increased the ULV, resulting in an expansion of the VF induction window during the vulnerable period. © Med Sci Monit, 2008.